Motivational profile of undergraduates in chemistry from a sociocognitivist perspective: considering gender and institutional programs (Research, Society and Development, 2022)
This study aimed to analyze the motivational profile of undergraduates in Chemistry in the city of Manaus, considering factors such as gender and participation in institutional programs. To do so, we adopted a mixed research approach that enables dialogue and integration between quantitative and qualitative data. The research had the participation of 58 students from two higher education federal institutions. Data were collected through the application of a questionnaire formed by items that evaluated different motivational levels proposed by the Theory of Self-Determination. In addition, we used semi-structured interviews to better understand the factors that influenced the participants' motivational profile. Regarding the questionnaire, the data were treated using descriptive and inferential statistics, while the speeches were analyzed according to the assumptions of Discursive Textual Analysis. The results showed a little self-determined motivational profile with higher averages for items that assessed extrinsic motivation by introjected regulation. Based on this understanding, it is possible to develop strategies and actions that favor permanence in the course, good performance and well-being in the training contexts. In this way, we hope that this research can contribute to promoting discussions about the importance of motivation in the formation of chemistry teachers.